2021
DOI: 10.1007/s00401-021-02382-4
|View full text |Cite
|
Sign up to set email alerts
|

EZHIP: a new piece of the puzzle towards understanding pediatric posterior fossa ependymoma

Abstract: Ependymomas (EPN) are tumors of the central nervous system (CNS) that can arise in the supratentorial brain (ST-EPN), hindbrain or posterior fossa (PF-EPN) or anywhere in the spinal cord (SP-EPN), both in children and adults. Molecular profiling studies have identified distinct groups and subtypes in each of these anatomical compartments. In this review, we give an overview on recent findings and new insights what is driving PFA ependymomas, which is the most common group. PFA ependymomas are characterized by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 91 publications
(224 reference statements)
1
17
0
Order By: Relevance
“…A molecular subclass of posterior fossa ependymomas (PFA ependymomas) with so far unknown cellular origin (Jenseit et al, 2022) has been reported to exhibit global reduction of H3K27me3 and hypermethylation of CpG islands (Bayliss et al, 2016), similar to the described epigenetic landscape of DIPG tumors expressing H3K27M (reviewed by Jenseit et al (2022)). Interestingly, transcriptomic analyses of PFA ependymomas revealed a subset of tumors expressing a so far uncharacterized protein encoded by the gene CXORF67 (Pajtler et al, 2018), subsequently named EZHIP (enhancer of zeste homologs inhibitory protein) (Jain et al, 2019) or CATACOMB (catalytic antagonist of Polycomb) (Piunti et al, 2019).…”
Section: Ependymomasmentioning
confidence: 97%
“…A molecular subclass of posterior fossa ependymomas (PFA ependymomas) with so far unknown cellular origin (Jenseit et al, 2022) has been reported to exhibit global reduction of H3K27me3 and hypermethylation of CpG islands (Bayliss et al, 2016), similar to the described epigenetic landscape of DIPG tumors expressing H3K27M (reviewed by Jenseit et al (2022)). Interestingly, transcriptomic analyses of PFA ependymomas revealed a subset of tumors expressing a so far uncharacterized protein encoded by the gene CXORF67 (Pajtler et al, 2018), subsequently named EZHIP (enhancer of zeste homologs inhibitory protein) (Jain et al, 2019) or CATACOMB (catalytic antagonist of Polycomb) (Piunti et al, 2019).…”
Section: Ependymomasmentioning
confidence: 97%
“…A potentially druggable pathway in PFA EPN is EZHIP, although direct targeting of EZHIP might prove difficult to achieve, because no enzymatic activity has hitherto been identified [ 207 ]. High EZHIP expression sensitizes to PARP inhibitors by inhibiting homologous recombination-mediated DNA repair, especially in combination with radiotherapy, indicating this treatment approach as potentially beneficial in PFA [ 208 ].…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…Indeed, blockade of FGFR by dominant-negative and pharmacological inhibitors impairs cell survival and stemness features in ST-RELA cells [ 165 , 218 ] Simultaneous inhibition of CDK4/6-CCND2 (with palbociclib) and IGF2/IGF1R (with ceritinib) pathways results in combinatorial drug efficacy, highlighting that targeting distinct subpopulations may be a successful therapeutic option [ 165 ]. CDK4/6 has also been proposed as an actionable driver in PFA, because the tumor suppressor gene CDKN2A , which codes for the CDK4/6 inhibitor p16, is epigenetically silenced by H3K27 trimethylation in PFA [ 146 , 207 ]. A phase 1 trial is addressing the safety and tolerability of the CDK4/6 inhibitor ribociclib in children and young adults with recurrent brain tumors, including EPN (NCT03434262).…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations